Integrated assessment of differentially expressed plasma microRNAs in subtypes of nonsyndromic orofacial clefts. Issue 25 (June 2018) - Wu, Ni; Yan, Jun; Han, Tao; Zou, Jijun; Shen, Weimin
Abstract: Background: Orofacial clefts include cleft lip only (CLO), cleft palate only (CPO), and cleft lip with palate (CLP). Previously, we reported the expression profile of plasma microRNAs in CLO, CPO, and CLP, respectively. However, the interaction of each subtype remains poorly investigated. Methods: In this study, we integrated the expression profiles of plasma miRNAs in these 3 subtypes, and assessed the distinct and overlapping dysregulated miRNAs using Venn diagrams. Their respective target genes reported in the literature were further analyzed using pathway analysis. Results and conclusion: The results showed that distinct or overlapping signaling pathways were involved in CLO, CPO, and CLP. The common key gene targets reflected functional relationships to the Wnt, Notch, TGF-beta, and Hedgehog signaling pathways. Further studies should examine the mechanism of the potential target genes, which may provide new avenues for future clinical prevention and therapy. Abstract : Supplemental Digital Content is available in the text